A fire-resistant polyamide composition and its preparation method and application
By adopting fire-resistant polyamide compositions, the problems of flammable aluminum alloy at high temperatures and low thermal conductivity of traditional flame-retardant materials are solved, and the preparation of high thermal conductivity and refractory materials can be achieved, which can effectively prevent fires caused by thermal runaway from the battery.
Patent Information
- Application Number
- CN202311746969.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-12-19
AI Technical Summary
The existing battery housing material aluminum alloy is flammable at high temperatures, while the traditional flame-retardant polymer materials have low thermal conductivity and insufficient fire resistance, which cannot effectively prevent fires caused by thermal runaway from the battery.
A fire-resistant polyamide composition is adopted, which includes components such as aliphatic polyamide, halogen-free flame retardant, glass fiber and triscilite, and heated melt blended and extruded by a single screw or twin screw extruder to form a material with high thermal conductivity and fire resistance.
The polyamide composition can last for more than 10 minutes in a flame of 1000°C without melting or losing structural strength, significantly improving the flame retardant performance and heat dissipation ability of the battery case, and providing passengers with sufficient escape time in the case of thermal runaway.
Smart Images

Figure CN117736576B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a fireproof polyamide composition and a preparation method and application thereof. Background Art
[0002] In recent years, the new energy vehicle industry has entered a stage of vigorous development. New energy vehicle companies have used lithium batteries on a large scale in power batteries. Lithium batteries are high-energy bodies, and their charging and discharging is a violent heating process. Thermal runaway is one of the most common safety hazards of lithium batteries. Internal short circuits, overcharging, overdischarging and high temperatures are the main causes of thermal runaway. Thermal runaway of electric vehicles can cause battery combustion and surrounding parts to catch fire, and even explosions in severe cases.
[0003] Government regulators and OEMs hope to reduce the accident rate of batteries to the lowest value within a controllable range through various stringent standards. The Chinese standard "GB 38031-2020 Safety Requirements for Power Batteries for Electric Vehicles" requires that after a thermal runaway occurs in an electric vehicle battery cell, the battery system will not catch fire or explode within 5 minutes, which helps ensure that the driver has enough time to evacuate and extinguish the fire. This requires that the battery pack casing has excellent flame retardant properties and can effectively delay the spread of flames in the event of an electric vehicle fire. The improvement of regulations and safety standards will accelerate the technical improvement of related products, further enhance product quality and ensure product safety through technological innovation.
[0004] Aluminum alloy is currently the main material for battery casings. Aluminum alloy has advantages such as high strength and excellent heat dissipation, but its disadvantages cannot be ignored. Aluminum alloy casings have a large specific gravity and a complex manufacturing process. In addition, aluminum is highly chemically reactive with water at high temperatures, so it is difficult to extinguish a fire with water. Improper handling can lead to greater disasters. Traditional flame-retardant polymers usually use bromine, inorganic phosphorus or organic phosphorus to provide flame suppression, but this material can only support tens of seconds when exposed to flames and cannot meet the needs of power battery thermal runaway application scenarios. Moreover, the thermal conductivity of traditional flame-retardant polymer materials is relatively low, and there is also a heat dissipation problem when used in battery casings. Poor heat dissipation will lead to loss of battery life.
[0005] As one of the most ideal materials for lightweight and efficient structural design, polyamide composite materials have the advantages of high specific strength, corrosion resistance, fatigue resistance, good dimensional stability and strong design, and are very suitable for replacing aluminum alloys for battery pack housings and covers. Flame-retardant modified polyamide compositions usually add sufficient flame retardants to the formula to achieve flame suppression performance, such as patent document CN110461929A discloses a phosphite flame-retardant polyamide, patent document CN103328572A discloses a red phosphorus flame-retardant polyamide, and patent document CN102089373A discloses a melamine urate flame-retardant polyamide. However, these traditional flame-retardant polyamide composite materials can only resist flame burning for tens of seconds, and the flame retardant performance needs to be further improved. Patent document CN113646162A discloses a flame-retardant heat-insulating material suitable for battery cells, which has a three-layer structure, with aromatic polyamide and mica paper as the outer layer, and the inner layer is inorganic short fiber felt or paper. This method can well block the flame, but the disadvantage is that the design freedom of the product is not high. Patent document CN106133043A discloses a polyamide-based composition with fillers from the group comprising aluminum oxide, boron nitride and aluminum silicate, which is used to manufacture products with higher fire protection requirements, especially preferably products with higher glow wire (GWFI) requirements. This polyamide composite material is capable of contacting a glow wire (GWFI) of 960°C / 30 seconds, but is still far from blocking the flame for more than 5 minutes. The known molding composition is still insufficient to effectively delay the spread of flame, and a composition with sufficient structural strength in a high temperature environment has not been provided. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the main purpose of the present invention is to provide a fire-proof polyamide composition, which is a polyamide composite material that can replace aluminum alloy for heat dissipation, will not melt, drip or perforate even when burned by flame for at least 5 minutes, and still has a certain structural strength in the flame.
[0007] Another object of the present invention is to provide a method for preparing the fire-resistant polyamide composition.
[0008] Another object of the present invention is to provide an application of the fireproof polyamide composition in the preparation of a new energy vehicle lithium battery pack housing and a cover.
[0009] To achieve the above object, the present invention adopts the following technical solution:
[0010] The present invention provides a fire-resistant polyamide composition, comprising the following components:
[0011]
[0012] The total of components (A) to (F) is 100 wt%.
[0013] Preferably, component (A) is an aliphatic polyamide and / or a semi-aromatic polyamide.
[0014] More preferably, the repeating units of the aliphatic polyamide are selected from one or more monomers of aliphatic dicarboxylic acids, aliphatic diamines having not less than four carbon atoms, and lactams; wherein:
[0015] The aliphatic dicarboxylic acid is selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid;
[0016] The aliphatic diamine having not less than four carbon atoms is selected from the group consisting of butanediamine, pentamethylenediamine, ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine;
[0017] The lactam is selected from the group consisting of: ε-caprolactam, enantholactam, undecanolactam, dodecanolactam, α-pyrrolidone, and α-piperidone.
[0018] In some preferred embodiments, the aliphatic polyamide and monomer are selected from one or more of the following:
[0019] Aliphatic polyamide monomer PA 6 ε-Caprolactam PA 66 Hexamethylenediamine, adipic acid PA 610 Hexamethylenediamine, sebacic acid PA 612 Hexamethylenediamine, dodecanedioic acid PA 46 Butanediamine, adipic acid PA 56 Pentamethylenediamine, adipic acid PA 1010 Decanediamine, Sebacic acid PA 11 Undecanolactam PA 12 Dodecanolactam
[0020] In some preferred embodiments, the aliphatic polyamide is a semi-crystalline polymer having a melting temperature of 150-300° C. and is selected from one or a mixture of two or more of PA 6, PA 66, PA 66 / 6, PA 610, PA 612, PA 46, PA 56, PA 1010, PA 11 and PA12, preferably PA66 and / or PA 6.
[0021] Preferably, the repeating unit of the semi-aromatic polyamide is selected from one or more monomers of aromatic diamines, aromatic dicarboxylic acids, aliphatic dicarboxylic acids, diamines having not less than four carbon atoms, lactams, and aminocarboxylic acids; wherein:
[0022] The aromatic diamine is selected from the group consisting of the following substances: m-phenylenediamine, p-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 1,4-bis(aminomethyl)naphthalene, 1,5-bis(aminomethyl)naphthalene, 2,6-bis(aminomethyl)naphthalene, 2,7-bis(aminomethyl)naphthalene, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ether;
[0023] The aromatic dicarboxylic acid is selected from the group consisting of the following substances: terephthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 1,3-phenylenedioxy diacetic acid, 1,4-phenylenedioxy diacetic acid, 4,4'-oxydibenzoic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylethane-4,4'-dicarboxylic acid, diphenylpropane-4,4'-dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, diphenyl sulfone-4,4'-dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-triphenyl dicarboxylic acid;
[0024] The aliphatic dicarboxylic acid is selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid;
[0025] The diamine having not less than four carbon atoms is selected from the group consisting of butanediamine, pentanediamine, ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, aliphatic diamines such as 1,3-cyclohexyldiamine, 1,4-cyclohexyldiamine, bis(4-aminocyclohexyl)methane, bis(4-aminocyclohexyl)propane, bis(3-methyl-4-aminocyclohexyl)methane, (3-methyl-4-aminocyclohexyl)propane, 1,3-diaminomethylcyclohexane, 1,4-diaminomethylcyclohexane, 5-amino-2,2,4-trimethyl-1-cyclopentanemethylamine, 5-amino-1,3,3-trimethylcyclohexanemethylamine, bis(aminopropyl)piperazine, bis(aminoethyl)piperazine, norbornanedimethylamine, etc.;
[0026] The lactam is selected from the group consisting of the following substances: ε-caprolactam, enantholactam, undecanolactam, dodecanolactam, α-pyrrolidone, α-piperidone;
[0027] The aminocarboxylic acid is selected from the group consisting of 6-aminohexanoic acid, 7-aminoheptanoic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid.
[0028] In some preferred embodiments, the semi-aromatic polyamide and monomer are selected from one or more of the following:
[0029] Semi-aromatic polyamide monomer PA 9T Nonanediamine and terephthalic acid PA 10T Decanediamine and terephthalic acid PA 12T Dodecanediamine and terephthalic acid PA 4T / 6T / 66 Butanediamine, hexamethylenediamine, adipic acid and terephthalic acid PA 5T / 56 Pentamethylenediamine, adipic acid and terephthalic acid PA 6T / 66 Hexamethylenediamine, adipic acid terephthalic acid PA 6T / 6 Hexamethylenediamine, adipic acid and ε-caprolactam PA 6T / 6I Hexamethylenediamine, terephthalic acid and isophthalic acid PA 6T / 6I / 66 Hexamethylenediamine, adipic acid, terephthalic acid and isophthalic acid PA 6T / DT Hexamethylenediamine, 2-methylpentamethylenediamine and terephthalic acid PA 6T / 10T Hexamethylenediamine, decanediamine and terephthalic acid PA 10T / 10I Decanediamine, terephthalic acid and isophthalic acid
[0030] In some preferred embodiments, the semi-aromatic polyamide is PA 6T / 66.
[0031] Preferably, component (B) is a halogen-free flame retardant, which is a dialkyl phosphinate represented by formula (I); or a mixture of a dialkyl phosphinate represented by formula (I) and a phosphite represented by formula (II); or a mixture of a dialkyl phosphinate represented by formula (I), melamine polyphosphate and zinc borate;
[0032]
[0033] In formula (I), R 1 , R 2 are the same or different and represent a linear or branched C1-C6 alkyl group;
[0034] M1 represents Mg, Ca, Al, Sb, Sn, Ge, Ti, Zn, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K and / or a protonated nitrogen base; m represents an integer from 1 to 4; n represents an integer from 1 to 4;
[0035]
[0036] In formula (II), M2 represents Mg, Ca, Al, Sb, Sn, Ge, Ti, Zn, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K; m represents an integer from 1 to 4.
[0037] The halogen-free flame retardants represented by formula (I) and (II) are described in patent CN103154110B and can be purchased commercially.
[0038] More preferably, when the halogen-free flame retardant is a mixture, the content of the dialkyl phosphinate represented by formula (I) is higher than 70%, preferably higher than 80%, and more preferably higher than 90%.
[0039] In some embodiments, the flame retardant is aluminum diethylphosphinate 3 (C4H 10 O2P).Al), or diethylphosphinate aluminum 3 (C4H 10A mixture of Al and aluminum hypophosphite Al2(HPO3)3, or diethylphosphinate aluminum 3(C4H 10 O2P).Al, melamine polyphosphate and zinc borate. When the halogen-free flame retardant is a mixture, diethylphosphinate aluminum 3 (C4H 10 O2P).Al ratio is higher than 70%, preferably higher than 80%, more preferably higher than 90%.
[0040] Preferably, component (C) is glass fiber selected from round cross-section glass fiber and / or flat cross-section glass fiber.
[0041] The flat cross-section glass fiber refers to a glass fiber with a certain thickness-to-width ratio cross section, and the cross section can have a variety of shapes, including rectangular, elliptical and approximately elliptical, and the shape ratio (ratio of the short axis length to the long axis length) is in the range of 1:1.5 to 6, more preferably in the range of 1:2 to 5, and more preferably in the range of 1:3 to 4.
[0042] Preferably, component (D) is a ceramic mineral selected from at least 60 wt% of kyanite and 0 to 40 wt% of one or more of spherical alumina, titanium dioxide and boron nitride; wherein:
[0043] The kyanite is a triclinic aluminum silicate mineral with a chemical formula of A2SiO5 and a typical chemical composition of 63.3% Al2O3 and 36.7% SiO2. The term "triclinic system" is understood by ordinary technicians in the field to mean a crystal structure with neither a higher-order symmetry axis nor a secondary axis and a symmetry plane, and its three crystal axes are mutually oblique, the unit cell axis distance a≠b≠c, and the axis angle α≠β≠γ≠90°( Figure 2 ). Triclinic kyanite is an unstable phase at high temperature and has a low sintering temperature. When the heating temperature exceeds 1100°C, it decomposes into mullite and fused silica glass through the following reactions:
[0044] 3(Al2O3·SiO2)→3Al2O3·2SiO2+SiO2
[0045] This transformation helps to increase the load softening temperature and compressive strength, which can provide supporting strength for the product in the flame.
[0046] Preferably, component (E) is a flux, which functions to reduce the sintering temperature of the ceramic filler, that is, to promote liquid phase vitrification of the ceramic filler at a lower temperature. The flux is selected from alkaline earth metal oxides, rare earth oxides, or any combination thereof.
[0047] Alkaline earth metals refer to Group IIA elements in the periodic table, including six metal elements, namely beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba) and radium (Ra). From the perspective of easy and cheap raw material acquisition and safe use, the alkaline earth metal oxide is selected from magnesium oxide (MgO), calcium oxide (CaO) and barium oxide (BaO), preferably MgO.
[0048] Rare earth elements are 17 elements, including scandium (Sc), element 21, and yttrium (Y), element 39 of the third subgroup of the periodic table, and lanthanide elements lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and yttrium (Y). From the perspective of easy and cheap acquisition of raw materials and safe use, the rare earth oxide is selected from cerium oxide (CeO2), lanthanum oxide (La2O3), yttrium oxide (Y2O3), and scandium oxide (Sc2O3), preferably Y2O3.
[0049] The amount of flux added should be appropriately set in consideration of the content of the ceramic mineral in the composition. The ratio of the amount of flux added to the amount of the ceramic mineral added is preferably set to 0.02 to 0.2, and more preferably to 0.05 to 0.1.
[0050] Preferably, component (F) is other auxiliary agents, selected from one or a mixture of two or more of a colorant, a release agent, a heat stabilizer, a flow improver and a crystallization accelerator.
[0051] The present invention also provides a method for preparing the fireproof polyamide composition, which is obtained by heating, melting, blending and extruding through a single-screw or twin-screw extruder.
[0052] Preferably, the length-to-diameter ratio (L / D) of the single-screw or twin-screw extruder is 32-52, preferably L / D is 40-44.
[0053] Preferably, the processing temperature is set to 150-300° C., and the screw speed is set to 200-500 rpm.
[0054] Preferably, the process of heating, melting, blending and extruding comprises:
[0055] Feeding sequence: a side feeding port is set at the rear section of the single-screw or twin-screw extruder for heating and melting, and component (B) flame retardant and component (C) glass fiber are added. Other material components are metered and added from the main feeding port of the extruder after premixing;
[0056] Exhaust: 1 to 2 barrel holes in front of the extruder feeding port are used for normal pressure exhaust, and the second to last barrel hole in the die head is used for pressurized exhaust, with a pressure range of 30 to 70 cm-Hg;
[0057] The melt from the twin-screw extruder is extruded through a die, cooled in a water tank, and cut into granules by a pelletizer. The collected granules are dried to a moisture content of less than 0.1% and then packaged.
[0058] The present invention also provides the use of the fireproof polyamide composition in preparing a housing and a cover of a lithium battery pack for a new energy vehicle.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] The fireproof polyamide composition of the present invention is filled with a thermally conductive filler mainly composed of triclinic kyanite, and its thermal conductivity is improved by several to dozens of times compared with traditional polymer materials, which can improve heat dissipation and help reduce thermal runaway of the battery. In addition, the sintering temperature of triclinic minerals is relatively low, and with the aid of flux, it can be vitrified in a flame of 1000°C, providing support strength for the product in the flame. According to tests, the fireproof polyamide composition can withstand direct flame exposure at 1000°C for more than 10 minutes, which can provide passengers with enough time to leave the vehicle when thermal runaway occurs. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 Schematic diagram of flame exposure test of the specimen in the embodiment.
[0062] Figure 2 Schematic diagram of the crystal structure model of triclinic kyanite. DETAILED DESCRIPTION
[0063] The present invention is further described by the following examples. It should be understood that the following examples are for illustrative purposes only and are not intended to limit the present invention.
[0064] The following materials were used in the Examples and Comparative Examples:
[0065] PA 66: Polyamide 66 produced by Ningxia Ruitai Company, brand YN27400.
[0066] PA 6: Polyamide 6 produced by Luxi Chemical Company, brand LX275.
[0067] PA 6T / 66: Polyamide 66 / 66 produced by Jinlun Company, brand A520.
[0068] MPA: refers to a mixture of PA 610: PA 612: PA 46: PA 56: PA 1010: PA 11: PA 12 in the ratio of 1:1:1:1:1:1:1, obtained by Jinlun Company.
[0069] MPPA: refers to a mixture of PA 9T: PA 10T: PA 12T: PA 4T / 6T / 66: PA 5T / 56: PA 6T / 6: PA 6T / 6I: PA6T / 6I / 66: PA 6T / DT: PA 6T / 10T: PA 10T / 10I in the ratio of 1:1:1:1:1:1:1:1:1:1:1:1, obtained by Jinlun Company.
[0070] GF-1: Round cross-section glass fiber 995-10P produced by Shandong Fiberglass Company, with a single fiber diameter of 10μm.
[0071] GF-2: Flat glass fiber ECS301HP-3-M4 produced by Chongqing International Composite Materials Co., Ltd., with a profile ratio of 1:4.
[0072] FR-1: Aluminum diethylphosphinate produced by Clariant, brand OP1230.
[0073] FR-2: A mixture of aluminum diethylphosphinate, melamine polyphosphate and zinc borate produced by Clariant, with the proportion of aluminum diethylphosphinate being about 70% to 80%. OP1314.
[0074] FR-3: A mixture of aluminum diethylphosphinate and aluminum hypophosphite produced by Clariant, with the proportion of aluminum diethylphosphinate being about 90%. 1400.
[0075] Kyanite: Kyanite from American Kyanite Mining, 100 mesh.
[0076] Al2O3: Spherical alumina produced by Yishitong Company.
[0077] TiO2: Rutile titanium dioxide produced by Coster, Australia, brand RCL-69.
[0078] BN: Boron nitride produced by 3M Company in the United States, brand CFA50M.
[0079] MMD: refers to a mixture of Al2O3:TiO2:BN in a ratio of 1:1:1, obtained by Jinlun Company.
[0080] MgO: magnesium oxide produced by Kyowa Chemical of Japan, brand MF-150.
[0081] CaO: Calcium oxide from commercial sources, analytical grade.
[0082] BaO: from commercially available barium oxide, analytical grade.
[0083] CeO2: from commercially available cerium oxide, analytical grade.
[0084] La2O3: from commercially available lanthanum oxide, analytical grade.
[0085] Sc2O3: from commercially available scandium oxide, analytical grade.
[0086] Y2O3: from commercially available yttrium oxide, analytical grade.
[0087] MMO: refers to a mixture of CaO:BaO:CeO2:La2O3:Sc2O3 in the ratio of 1:1:1:1:1, obtained by Jinlun Company.
[0088] 1098: Antioxidant 1098 produced by BASF, with the chemical name N,N'-bis-(3-(35-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.
[0089] Black MB: PA6 carrier / 40% carbon black masterbatch SC8715 produced by Ningbo Masterbatch Factory.
[0090] CaSt2: refers to calcium stearate SAK-CS-P produced by Singapore Samyuk Company.
[0091] Preparation method
[0092] The components were weighed according to the composition shown in Table 1 and then added into a twin-screw extruder for melt processing.
[0093] Extruder screw nominal diameter: 35mm;
[0094] Extruder screw aspect ratio: 40;
[0095] Processing temperature range: 150~300℃;
[0096] Main engine speed range: 300rpm;
[0097] Feeding sequence: Set a side feeding port at the rear section of the extruder for heating and melting, add flame retardant and glass fiber, and add other material components through the main feeding port of the extruder after premixing.
[0098] Exhaust: 1 to 2 barrel openings in front of the extruder feeding port are used for normal pressure exhaust, and the second to last barrel opening in the die head is used for pressurized exhaust. The pressure range is 30 to 70 cm-Hg.
[0099] The melt from the twin-screw extruder is extruded through a die, cooled in a water tank, and cut into granules by a pelletizer. The collected granules are dried to a moisture content of less than 0.1% and then packaged.
[0100] Specimen molding and conditioning
[0101] The specimens were molded and conditioned according to the method specified in ISO16396-2, with a melt temperature of 250-300°C and a mold temperature of 80-100°C. For the mechanical properties test, the specimens were placed in a 23°C environment for more than 16 hours, and the moisture content of the specimens was ensured to be less than 0.2%. For the flammability test, the specimens were subjected to two pre-conditioning conditions: 23°C / 50%RH / 48 hours and 70°C / 168 hours.
[0102] Thermal conductivity test
[0103] Thermal conductivity refers to the amount of heat transferred through an area of 1 square meter in 1 second under stable heat transfer conditions when the temperature difference between the two surfaces of a 1m thick material is 1 degree (K, ℃). It is represented by the symbol λ and its unit is W / (mK).
[0104] The thermal conductivity calculation formula is λ=ρ×a×Cp, where:
[0105] ρ-Material density, measured by immersion method;
[0106] a- thermal diffusion coefficient, measured by laser flash method;
[0107] Cp-specific heat capacity, measured by DSC method.
[0108] Flammability test
[0109] The V-level vertical combustion test was carried out according to the method specified in UL94. The test piece size was 125mm×13.0mm×1.5mm, the flame height of the methane blowtorch was 20mm, the inner flame height was 10mm, and the test instrument was the ATLAS HVUL2 combustion box.
[0110] Flame exposure test
[0111] The flame height of the methane blowtorch is 125 mm, the inner flame height is 40 mm, the flame temperature is 1000°C, the blowtorch angle is 20±5°, and the test instrument is the ATLAS HVUL2 combustion box.
[0112] Two sizes of test pieces are provided for testing: the test piece used to evaluate appearance is 80mm×80mm×2mm, and the test piece used to evaluate mechanical properties is 80mm×10mm×4.0mm.
[0113] As shown in Figure (1), during the test, the test piece is fixed horizontally and the height is adjusted so that the inner flame of the flame contacts the center of the sample. If the test piece is cracked or perforated after contact with the flame, the test is stopped and the time is recorded.
[0114] Mechanical properties test
[0115] The bending performance was tested according to the method specified in ISO 178. The test piece size was 80 mm × 10 mm × 4 mm. The pressing speed was 2 mm / min. The testing instrument was a ZWICK Z010 universal testing machine.
[0116] Examples and Comparative Examples
[0117] Tables 1 and 2 list the performance tests of the compositions of various examples.
[0118] Compared with Comparative Examples 1, 4 and 5, Comparative Example 4 does not add glass fiber and ceramic minerals, Comparative Example 1 adds 30% glass fiber, and Comparative Example 5 adds 30% kyanite. The vertical combustion rating of the three comparative examples can reach V-0 level according to UL94 evaluation. However, the flame exposure test results show that the fire resistant performance of Comparative Example 5 with added kyanite is better than that of Comparative Example 1 with added glass fiber, and even better than that of Comparative Example 4 without added filler.
[0119] Compared with Comparative Example 1 and Example 1, Example 1 adds 20% kyanite and 1% magnesium oxide relative to the composition of Comparative Example 1. It can be observed that the advantages brought about by this are that the thermal conductivity of Example 1 is increased by 5 times, from 0.2W / (mK) to 1.0W / (mK), and the flame exposure fire resistance is increased by more than 10 times, from being unable to support 1 minute to being structurally intact after exposure for 10 minutes.
[0120] Compared with Example 1 and Example 2, the flux of Example 2 is yttrium oxide, and the mechanical properties tested after flame exposure are slightly better than that of Example 1 using magnesium oxide.
[0121] Compared with Example 2, Example 3 and Example 4, the proportion of ceramic filler increases successively. When the ceramic filler increases from 20% to 40%, it is observed that the flame exposure performance is improved. However, when the ceramic filler is further increased to 60%, the performance decreases instead. Since the combination needs to ensure processability, the increase in the proportion of ceramic filler requires the reduction of glass fiber.
[0122] Compared with Comparative Examples 6 and 7 and Examples 6-10, when the proportion of flux increases, it can be found that the flame retardant performance of the composition decreases, and the V-0 flame retardant grade cannot be stably achieved. Flame retardant performance is a critical indicator for battery peripheral products, and the flame retardant grade of the composition must be guaranteed to be above V2. Therefore, the proportion of flux needs to be controlled within a reasonable range.
[0123] Table 1
[0124]
[0125]
[0126] Note: Appearance evaluation: O = structural integrity; △ = obvious structural deformation; × = structural failure (burn through or melt).
[0127] Table 2
[0128]
[0129] The above is only a preferred embodiment of the present invention, but the present invention should not be limited to the contents disclosed in the embodiment. Therefore, any equivalent or modification completed without departing from the spirit disclosed in the present invention shall fall within the scope of protection of the present invention.
Claims
1. A fire-resistant polyamide composition, characterized in that: The polyamide composition comprises the following components: Wherein, the sum of components (A) to (F) accounts for 100wt% of the total amount of the polyamide composition; The polyamide is an aliphatic polyamide and / or a semi-aromatic polyamide; The repeating units of the aliphatic polyamide are selected from one or more monomers derived from aliphatic dicarboxylic acids, aliphatic diamines having not less than four carbon atoms, and lactams; wherein: The aliphatic dicarboxylic acid is selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid; The aliphatic diamine having not less than four carbon atoms is selected from the group consisting of butanediamine, pentamethylenediamine, ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine; The lactam is selected from the group consisting of the following substances: ε-caprolactam, enantholactam, undecanolactam, dodecanolactam, α-pyrrolidone, α-piperidone; The flame retardant is a halogen-free flame retardant selected from a dialkyl phosphinate represented by formula (I); or a mixture of a dialkyl phosphinate represented by formula (I) and a phosphite represented by formula (II); or a mixture of a dialkyl phosphinate represented by formula (I), melamine polyphosphate and zinc borate; ; In formula (I), R 1 , R 2 are the same or different and represent a linear or branched C1-C6 alkyl group; M1 represents Mg, Ca, Al, Sb, Sn, Ge, Ti, Zn, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K and / or a protonated nitrogen base; m represents an integer from 1 to 4; n represents an integer from 1 to 4; ; In formula (II), M2 represents Mg, Ca, Sn, Zn; m is 2; When the halogen-free flame retardant is a mixture, the content of the dialkyl phosphinate represented by formula (I) is higher than 70%; The ceramic mineral is selected from a mixture of at least 60 wt% of kyanite and 0 to 40 wt% of one or more of spherical alumina, titanium dioxide and boron nitride, wherein the kyanite is a triclinic aluminum silicate mineral with a chemical formula of Al2SiO5 and a chemical composition of 63.3% Al2O3 and 36.7% SiO2; The flux is selected from one or more of alkaline earth metal oxides and / or rare earth oxides; wherein: the alkaline earth metal oxide is selected from one or more of MgO, CaO and BaO; the rare earth oxide is selected from one or more of CeO2, La2O3, Y2O3 and Sc2O3, and the ratio of the added amount of the flux to the added amount of the ceramic mineral is 0.02~0.
2.
2. The fireproof polyamide composition according to claim 1, characterized in that: The aliphatic polyamide and monomer are selected from one or more of the following: PA 6, the monomer is ε-caprolactam; PA 66, the monomer is hexamethylenediamine and adipic acid; PA 610, the monomer is hexamethylenediamine and sebacic acid; PA 612, the monomer is hexamethylenediamine and dodecanedioic acid; PA 46, the monomer is butanediamine and adipic acid; PA 56, the monomer is pentamethylenediamine and adipic acid; PA 1010, the monomer is decanediamine and sebacic acid; PA 11, the monomer is undecane lactam; PA 12, the monomer is dodecanedioic acid.
3. The fireproof polyamide composition according to claim 1 or 2, characterized in that: The aliphatic polyamide is PA66 and / or PA 6.
4. The fireproof polyamide composition according to claim 1, characterized in that: The repeating units of the semi-aromatic polyamide are selected from one or more monomers derived from aromatic diamines, aromatic dicarboxylic acids, aliphatic dicarboxylic acids, diamines having not less than four carbon atoms, lactams, and aminocarboxylic acids; wherein: The aromatic diamine is selected from the group consisting of the following substances: m-phenylenediamine, p-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 1,4-bis(aminomethyl)naphthalene, 1,5-bis(aminomethyl)naphthalene, 2,6-bis(aminomethyl)naphthalene, 2,7-bis(aminomethyl)naphthalene, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ether; and / or the aromatic dicarboxylic acid is selected from the group consisting of terephthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 1,3-phenylenedioxy diacetic acid, 1,4-phenylenedioxy diacetic acid, 4,4'-oxydibenzoic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylethane-4,4'-dicarboxylic acid, diphenylpropane-4,4'-dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, diphenyl sulfone-4,4'-dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-triphenyl dicarboxylic acid; and / or the aliphatic dicarboxylic acid is selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid; and / or the diamine having not less than four carbon atoms is selected from the group consisting of butanediamine, pentamethylenediamine, ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, or aliphatic diamines of 1,3-cyclohexyldiamine, 1,4-cyclohexyldiamine, bis(4-aminocyclohexyl)methane, bis(4-aminocyclohexyl)propane, bis(3-methyl-4-aminocyclohexyl)methane, (3-methyl-4-aminocyclohexyl)propane, 1,3-diaminomethylcyclohexane, 1,4-diaminomethylcyclohexane, 5-amino-2,2,4-trimethyl-1-cyclopentanemethylamine, 5-amino-1,3,3-trimethylcyclohexanemethylamine, bis(aminopropyl)piperazine, bis(aminoethyl)piperazine, and norbornanedimethylamine; and / or the lactam is selected from the group consisting of: ε-caprolactam, enantholactam, undecanolactam, dodecanolactam, α-pyrrolidone, α-piperidone; And / or the aminocarboxylic acid is selected from the group consisting of 6-aminohexanoic acid, 7-aminoheptanoic acid, 9-aminononanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid.
5. The fireproof polyamide composition according to claim 4, characterized in that: The semi-aromatic polyamide and monomer are selected from one or more of the following: PA 9T, the monomers are nonanediamine and terephthalic acid; PA 10T, the monomers are decanediamine and terephthalic acid; PA 12T, the monomers are dodecanediamine and terephthalic acid; PA 4T / 6T / 66, the monomers are butanediamine, hexamethylenediamine, adipic acid and terephthalic acid; PA 5T / 56, the monomers are pentamethylenediamine, adipic acid and terephthalic acid; PA 6T / 66, the monomers are hexamethylenediamine, adipic acid and terephthalic acid; PA 6T / 6, the monomers are hexamethylenediamine, adipic acid and ε-caprolactam; PA 6T / 6I, the monomers are hexamethylenediamine, terephthalic acid and isophthalic acid; PA 6T / 6I / 66, the monomers are hexamethylenediamine, adipic acid, terephthalic acid and isophthalic acid; PA 6T / DT, the monomers are hexamethylenediamine, 2-methylpentamethylenediamine and terephthalic acid; PA 6T / 10T, the monomers are hexamethylenediamine, decanediamine and terephthalic acid; PA 10T / 10I, the monomers are decanediamine, terephthalic acid and isophthalic acid.
6. The fireproof polyamide composition according to claim 5, characterized in that: The semi-aromatic polyamide is PA6T / 66.
7. The fireproof polyamide composition according to claim 1, characterized in that: The flame retardant is aluminum diethylphosphinate, or a mixture of aluminum diethylphosphinate and aluminum hypophosphite, or a mixture of aluminum diethylphosphinate, melamine polyphosphate and zinc borate; when the flame retardant is a mixture, the content of aluminum diethylphosphinate is higher than 70%.
8. The fireproof polyamide composition according to claim 1, characterized in that: The glass fiber is selected from circular cross-section glass fiber and / or flat cross-section glass fiber, wherein the cross-section of the flat cross-section glass fiber is selected from one or more of rectangular, elliptical and nearly elliptical shapes, and the profile ratio is 1:1.5-6; The flux is selected from one or more of alkaline earth metal oxides and / or rare earth oxides; wherein: The alkaline earth metal oxide is selected from one or more of MgO, CaO and BaO; and / or the rare earth oxide is selected from one or more of CeO2, La2O3, Y2O3 and Sc2O3; And / or the ratio of the amount of flux added to the amount of ceramic mineral added is 0.02-0.2; And / or the other auxiliary agent is selected from one or a mixture of two or more of a colorant, a release agent, a heat stabilizer, a flow improver and a crystallization accelerator.
9. The method for preparing the fire-resistant polyamide composition according to any one of claims 1 to 8, characterized in that: It is obtained by heating, melting, blending and extruding through a single-screw or twin-screw extruder; wherein: The single-screw or twin-screw extruder has an aspect ratio L / D of 32 to 52; The processing temperature is 150~300℃ and the screw speed is 200~500rpm.
10. The method for preparing the fireproof polyamide composition according to claim 9, characterized in that: The process of heating, melting, blending and extruding comprises: Feeding sequence: a side feeding port is set at the rear section of the single-screw or twin-screw extruder for heating and melting, and flame retardant and glass fiber are added. Other material components are metered and added from the main feeding port of the extruder after premixing; Exhaust: 1~2 barrel openings in front of the extruder feeding port are used for normal pressure exhaust, and the second-to-last barrel opening in the die head is used for pressurized exhaust, with a pressure range of 30~70cm-Hg; The melt from the twin-screw extruder is extruded through a die, cooled in a water tank, and cut into granules by a pelletizer. The collected granules are dried to a moisture content of less than 0.1% and then packaged.
11. Use of the fireproof polyamide composition according to any one of claims 1 to 8 in preparing a housing and a cover of a lithium battery pack for a new energy vehicle.
Citation Information
Patent Citations
Flame-retardant polyamide composition
CN102089373A
Flame retardant-stabilizer combination for thermoplastic polymers
CN103154110B
Flame-protected thermoplastic molding compound
CN103328572A
Flame-retardant polyamide compositions
CN106133043A
Flame-retardant polyamide molding compounds
CN110461929A